2005
DOI: 10.1016/j.ymthe.2005.06.096
|View full text |Cite
|
Sign up to set email alerts
|

Specific Regression of Human Cancer Cells by Ribozyme-Mediated Targeted Replacement of Tumor-Specific Transcript

Abstract: In this study, we describe a novel approach to human cancer therapy that is based upon trans-splicing ribozyme-mediated replacement of cancer-specific RNAs with new transcripts that exert therapeutic activities. We have developed a specific ribozyme that can reprogram human telomerase reverse transcriptase (hTERT) RNA to induce transgene activity selectively in cancer cells that express the RNA. The ribozyme-mediated triggering of the transgene expression was accomplished via a high-fidelity trans-splicing rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 30 publications
3
67
0
Order By: Relevance
“…In contrast, no accessible sites were found in the long hairpin-formed CUG repeat region. In previous studies, we showed that the relative trans-splicing reaction efficacy at different sites in a target RNA in cells and in vitro was closely associated with the predicted accessibility determined by mapping results (Ryu et al, 2003;Ryu and Lee, 2004;Kwon et al, 2005). Therefore, the ribozymes that target the ac-cessible sites identified here are anticipated to be more active than those that target other sites.…”
Section: Ribozyme-accessible Uridines In Mdmpk 3'-utr Rnamentioning
confidence: 53%
See 2 more Smart Citations
“…In contrast, no accessible sites were found in the long hairpin-formed CUG repeat region. In previous studies, we showed that the relative trans-splicing reaction efficacy at different sites in a target RNA in cells and in vitro was closely associated with the predicted accessibility determined by mapping results (Ryu et al, 2003;Ryu and Lee, 2004;Kwon et al, 2005). Therefore, the ribozymes that target the ac-cessible sites identified here are anticipated to be more active than those that target other sites.…”
Section: Ribozyme-accessible Uridines In Mdmpk 3'-utr Rnamentioning
confidence: 53%
“…To this end, we employed an RNA mapping strategy based on RNA tagging (Jones et al,1996) and a trans-splicing ribozyme library, which has been described in detail elsewhere (Fig. 1) (Lan et al, 1998;Lan et al, 2000;Kwon et al, 2005;Ryu et al, 2003;Song and Lee, 2007).…”
Section: Mapping Of the Trans-splicing Ribozymementioning
confidence: 99%
See 1 more Smart Citation
“…11,19 In brief, the Rib21AS ribozyme targeting U21 on the hTERT RNA was generated to harbor the extended internal guide sequence, which includes as an extension of the P1 helix, an additional 6-nt-long P10 helix, and a 325-nt-long antisense sequence complementary to the downstream region of the targeted hTERT RNA uridine. 11 cDNA as a 3 0 exon encoding for lacZ or herpes simplex virus thymidine kinase (HSVtk) genes was inserted into NruI/XbaI downstream of the modified group I intron expression construct. The resulting ribozyme was then cloned into pcDNA or pPEPCK-LCR (kindly provided by Dr K Oka from the Bayler College of Medicine).…”
Section: Generation Of Recombinant Adenoviral Vectorsmentioning
confidence: 99%
“…We validated this concept by developing transsplicing ribozymes targeting and replacing human telomerase reverse transcriptase (hTERT) RNA to induce transgene activity specifically in cancer cells that express the RNA, demonstrating that the ribozyme can specifically mark tumor cells expressing hTERT or specifically make tumor cells sensitive to prodrug treatment not only in vitro but in tumor xenografts. [11][12][13] This study showed that a trans-splicing ribozyme provides a multifunctional gene therapy tool that both targets and treats the tumor in two ways. A major advantage of this approach is that by invading a tumor-specific pre-mRNA, targeted expression of the therapeutic gene product is guaranteed, with a simultaneous reduction in the expression of the target gene product resulting in an additive, or perhaps a synergistic, anticancer effect.…”
Section: Introductionmentioning
confidence: 99%